Sensors and System for Vehicle Navigation - Andrzej Stateczny; Witold Kazimierski; Pawel Burdziakowski (Sensors, 2022)
In recent years, vehicle navigation, in particular autonomous navigation, has been at the center of several major developments, both in civilian and defense applications [...]